Perbedaan Hasil Belajar IPA dilihat dari Penggunaan Media Konkret dengan Media Audio-Visual pada Peserta Didik Kelas IV SDN-1 Panarung Palangkaraya - Desy Desy; Diplan Diplan (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to determine whether or not there are differences in learning outcomes of science seen from the use of concrete media with audio-visual media in fourth-grade students of SDN 1 Panarung 2015/2016 Academic Year. The research method in this study is a quantitative correlation. The results of the study show that there are differences in learning outcomes of science seen from the use of concrete media with audio-visual media in fourth-grade students of SDN 1 Panarung 2015/2016 Academic Year. with a count of t count of 6.012 and t table of 2,000 at N = 59 with a significant level of 5% for 2 tails which means tcount> t table or 6.012> 2,000.